(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2025)
It has been shown that under vibration conditions there is significant amidation of rat brain proteins, which is characteristic of inhibition processes. When studying the effect of Trifolium pratense L. (Red Clover) plants on the amidation of proteins under vibration conditions, it was shown that adding dry flowers of the plant to the animals’ diet leads to noticeable decrease in the amidation of brain proteins. The study showed that the T. pratense plant has a stress-protector effect under vibration conditions. Based on the conducted research, it is proposed to use the plant T. pratense in the development of broad-spectrum anti-stress drugs.